Erratum: Publisher Correction: A large intragenic deletion in the CLCN1 gene causes Hereditary Myotonia in pigs (Scientific reports (2019) 9 1 (15632)) - Araújo, C. E.T. [UNESP]; Oliveira, C. M.C.; Barbosa, J. D.; Oliveira-Filho, J. P. [UNESP]; Resende, L. A.L. [UNESP]; Badial, P. R.; Araujo-Junior, J. P. [UNESP]; Mccue, M. E.; Borges, A. S. [UNESP] (Springer Nature, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.